Strategi Penanganan Kredit Macet Pada Koperasi Karyawan BI SMK Yohanes XXIII Maumere - Arisandy Nau; Imanuel Wellem; Nunsio Handrian Meylano (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the strategies for handling bad debts at the Maju Terus Employee Cooperative at SMK Yohanes XXIII Maumere. The main problem faced by the cooperative is the increasing bad debts, most of which come from member arrears on daily transactions through the cash-on-account system, such as purchasing office stationery and photocopy services. This condition affects the cooperative's liquidity and reduces the effectiveness of services to members. The method used in this study is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation during internship activities. The research results indicate that the main causes of bad debts include low member discipline, lack of supervision, and weak credit management systems. Strategies that can be applied to address these issues include rescheduling payments, establishing stricter credit rules, increasing supervision, as well as providing guidance and education to members on the importance of responsibility in payments. The implementation of these strategies is expected to improve the quality of credit management, maintain the financial stability of the cooperative, and increase the members' welfare sustainably.